Estimating shear wave velocity using acceleration data in Antakya (Turkey) (2014)
This manuscript presents a site response analysis and an estimation of S-wave velocity that are dependent on acceleration data. First, existing data, such as density, seismic wave velocity, and soil cross-sections, are obtained from previous seismic microzonation studies and used to prepare input data for a suite of MATLAB routines, which are referred to as SUA software. Acceleration data are obtained from four free-field strong-motion stations of the SERAMAR project, which was conducted between 2006 and 2009 in conjunction with a Turkish-German joint research project, and inputted into the software as basic data. The results include a 1D velocity cross-section versus depth and an amplification model of the site. Three different depth levels can be determined for the ranges of 0-5 m, 5-15 m and 15-25 m. The seismic velocities vary between 380 and 470 m s-1 for the first 5 m; 320 and 480 m s-1 for 5-15 m; and 470 and 750 m s-1 for 15-25 m. These results are comparable with the amplification values from the microtremor data from previous studies. The 1D velocity models are appropriate for the soil conditions.ResumenEste trabajo presenta el análisis a una respuesta de sitio y una estimación de la velocidad de la onda de corte que son dependientes de la información de aceleración. Los datos adicionales como la densidad, la velocidad de onda sísmica y los cortes transversales de suelo, se obtuvieron de estudios previos de microzonificación sísmica y se utilizaron para preparar el registro de datos en una plataforma de rutinas MATLAB, que se refieren al software SUA. Los datos de información de la aceleración se tomaron de cuatro estaciones de monitoreo de movimientos fuertes a campo abierto del proyecto SERAMAR, que se realizó entre 2006 y 2009 en una investigación conjunta turco-alemana, y se ingresaron en el programa como la información básica. Los resultados incluyen una sección cruzada de velocidad 1D versus profundidad y el modelo amplificado del sitio. Se pudieron determinar tres niveles diferentes a partir de los rangos de 0-5 m, 5-15 m y 15-25 m. Las velocidades sísmicas pueden variar entre 380 y 470 m s-1 para los primeros 5 metros; 320 y 480 m s-1 para el rango 5-15 m, y 450 y 750 m s-1 para el rango 15-25 m. Estos resultados son comparables con los valores de amplificación del perfil Microtemor de estudios previos. Los modelos de velocidad 1D son apropiados para las condiciones del suelo.